Transformative expectations in research on environmental and sustainability education - Carlsson, Monica (Outlines. Critical Practice Studies, 2021)
While education in general is seen as a crucial means for creating social change and transformation, environmental and sustainability education (ESE) is especially subject to transformative expectations in tackling escalating societal problems such as the lack of sustainable development. This article explores how ESE research addresses transformative expectations and justifies the knowledge it produces and its methods. It first explores examples of this within three different categories focusing on: transformative teaching in higher education, systemic transformative change in higher education institutions, and transformative change agency formation in community settings. Thereafter follows a discussion of the interfaces between the examples when it comes to their ontological, epistemological and methodological stances. The analysis illustrates different ways of conceptualizing transformative expectations, drawing on terms such as ‘rethinking’, ‘revitalizing’, ‘disrupting’, ‘reframing’ and ‘transgressing’. It furthermore highlights two different foundations for methodological justifications in ESE research addressing transformative expectations: working for change within existing social frameworks (adaptation), or seeking improvement by transgressing norms (disruption). It is pointing out that such methodological justifications are likely to differ in terms of how they address change depending on whether the research is conducted within or outside formal education settings.